POLITIK BUDAYA TERHADAP MASSA APUNG: STUDI KASUS PESANTREN TRADISIONAL JAMIATUN BANTEN - Ulfah Fajarini (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2011)
Purpose of this article is pesantren in political constellation in indonesia, especially about cultural politic to floating mass, case study traditional pesantren Jamiahtun, Tangerang Banten. To collect field data, qualitatitive method was used by implementing participatory observation, in depth interview and library research. Investigation result is: relation between kiai and santri in Pesantren Jamiatun (PJ) is patron client. The interpretation and the use of religious doctrines in the PJ are carried out intensively and continuously in a quite long period by the religious elites so that conditions are established to facilitate the merger of the religious heavenly idealism of the followers and the idealism and the interest, of the elites which include some practical wordly political interest. In this research the pesantren was studied as phenomena of its kind which function as a floating mass in a culture political.